ISLAM DAN SISTIM MANAJEMEN PEREKONOMIAN MODERN - Difvi Rizka NH Siregar; Fifi Hasmawati (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
To be able to create a strong economy, independence is very important. This means independence to be able to produce goods to meet one's own needs, both material and non-material, for this, experience, ability and production facilities are needed. Apart from that, to meet needs in both the civil and military fields, various scientific disciplines, professions, crafts and skills are needed both in religious matters and in the world. Because Muslims must be able to study, deepen and teach as well as specialize themselves in various fields of knowledge. In this way Muslims are not dependent on others. The ability to be independent can be realized by being able to meet our own needs, without economic independence, Muslims cannot carry out the function of guiding the world (ustadziyah al-'alam). In Islam, as stated in the interpretation of verses and hadith, there is an economic management system.